2013
DOI: 10.4028/www.scientific.net/amr.873.683
|View full text |Cite
|
Sign up to set email alerts
|

Study on Synthesis and Property of Anti-Salt Super Absorbent Resin

Abstract: The maleic acid ( MA )2-acrylamido-2-methylpropanesulfonic acid (AMPS) and acrylamide (PAMPS/AM/MA) superabsorbent copolymer was synthesized by aqueous solution polymerization with ammonium persulfate as initiator,N,N-methylene-bisacrylamide ( NMBA) as crosslinking agent. The influence of pH,mass ratio of AMPS to acrylamide ( AM) ,the amount of crosslinking agent and initiator,and reaction temperature on the absorption capability of water and salt solution were investigated. The results show that the water abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The amount of water that a specific SAP can absorb depends on its chemical composition and morphology as well as the quality of absorbed water [ 41 ], particularly with respect to the presence of ionic salts. The recycled water used in mining plant operations generally contains a significant concentration of salts [ 42 ] that needs to be managed to maximize the polymeric absorption potential.…”
Section: Polymers Used In Mineral Processing and Metallurgymentioning
confidence: 99%
“…The amount of water that a specific SAP can absorb depends on its chemical composition and morphology as well as the quality of absorbed water [ 41 ], particularly with respect to the presence of ionic salts. The recycled water used in mining plant operations generally contains a significant concentration of salts [ 42 ] that needs to be managed to maximize the polymeric absorption potential.…”
Section: Polymers Used In Mineral Processing and Metallurgymentioning
confidence: 99%
“…SAP can be cationic and anionic. The amount of water that a specific SAP can absorb depends on its chemical composition and morphology as well as the quality of absorbed water [18], particularly with respect to occurrence of ionic salts. The recycled water used in mining plant operations generally contains a significant concentration of salts [19] and these need to be managed to maximize the polymeric absorption potential.…”
Section: Super Absorbent Polymers (Sap)mentioning
confidence: 99%
“…Acrylic acid (AA, K a = 5.6 × 10 −5 ) is a fairly cheap and common monomer [14], and 2-acrylamide-2-methyl propane sulfonic acid (AMPS) are anionic monomers consisting of a hydrophilic sulfonic acid group (K a = 2 × 10 −1 ) and a nonionic amide group [15], in which the non-ionic amide group gives the polymer better salt tolerance has attracted attention due to its stability, non-toxicity, and low cost [16]. The combination of both ionic hydrophilic groups (carboxyl groups, sulfonic acid groups, tertiary amine groups, etc) and nonionic hydrophilic groups (hydroxyl groups, ester groups, amide groups, etc) greatly improves the ability of salt tolerance and water absorption rate of the polymer [17]. Yeqiao Meng and Lin Ye have synthesized superabsorbent polymers based on starch and AA, AMPS has shown several advantages such as improved water absorption, swelling rate, high water retention, and salt tolerance [18,19], Elżbieta Czarnecka and co-workers showed that the -SO 3 H groups present in the AMPS groups of the potato starch-based superabsorbent polymer PVA/PS-g-P(AA-co-AM-co-AMPS) are responsible for the adsorption capacity higher water absorption than PVA/PS-g-P(AA-co-AM ) [20].…”
Section: Introductionmentioning
confidence: 99%